RHEOLOGY OF GRANITIC MAGMAS DURING ASCENT AND EMPLACEMENT - Petford N. (My University, 2003)
Considerable progress has been made over the past decade in under-standing the static rheological properties of granitic magmas in the continental crust. Changes in H 2 O content, CO 2 content, and oxidation state of the interstitial melt phase have been identified as important compositional factors governing the rheodynamic behavior of the solid/fluid mixture. Although the strengths of granitic magmas over the crystallization interval are still poorly constrained, theoretical investigations suggest that during magma ascent, yield strengths of the order of 9 kPa are required to com-pletely retard the upward flow in meter-wide conduits. In low Bagnold number magma suspensions with moderate crystal contents (solidosities 0.1 ≤ φ ≤ 0.3), viscous fluc-tuations may lead to flow differentiation by shear-enhanced diffusion. AMS and mi-crostructural studies support the idea that granite plutons are intruded as crystal-poor liquids (φ ≤ 50%), with fabric and foliation development restricted to the final stages of emplacement. If so, then these fabrics contain no information on the ascent (verti-cal transport) history of the magma. Deformation of a magmatic mush during pluton emplacement can enhance significantly the pressure gradient in the melt, resulting in a range of local macroscopic flow structures, including layering, crystal alignment, and other mechanical instabilities such as shear zones. As the suspension viscosity varies with stress rate, it is not clear how the timing of proposed rheological transitions formulated from simple equations for static magma suspensions applies to mixtures undergoing shear. New theories of magmas as multiphase flows are required if the full complexity of granitic magma rheology is to be resolved.
Keywords: granite magma; viscosity; melt fraction; solidosity; shear; granular ﬂow